2021
DOI: 10.1038/s41467-021-26079-0
|View full text |Cite
|
Sign up to set email alerts
|

A complex of BRCA2 and PP2A-B56 is required for DNA repair by homologous recombination

Abstract: Mutations in the tumour suppressor gene BRCA2 are associated with predisposition to breast and ovarian cancers. BRCA2 has a central role in maintaining genome integrity by facilitating the repair of toxic DNA double-strand breaks (DSBs) by homologous recombination (HR). BRCA2 acts by controlling RAD51 nucleoprotein filament formation on resected single-stranded DNA, but how BRCA2 activity is regulated during HR is not fully understood. Here, we delineate a pathway where ATM and ATR kinases phosphorylate a high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 62 publications
3
30
0
1
Order By: Relevance
“…Even though PP2A and RAD51 direct interaction has never been established and further studies are warranted to assess such hypothesis, published evidence has clearly demonstrated that PP2A plays an indirect role on RAD51’s activity and protein stability. The BRCA2–PP2A-B56 complex is essential for the efficient RAD51 filament formation at the sites of DNA damage(25). Furthermore, PLK1, which has been show to directly phosphorylate and activate RAD51’s recruitment(61), is dephosphorylated and inactivated by PP2A(62,63), reinforcing the idea that PP2A plays an indirect role on RAD51’s activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though PP2A and RAD51 direct interaction has never been established and further studies are warranted to assess such hypothesis, published evidence has clearly demonstrated that PP2A plays an indirect role on RAD51’s activity and protein stability. The BRCA2–PP2A-B56 complex is essential for the efficient RAD51 filament formation at the sites of DNA damage(25). Furthermore, PLK1, which has been show to directly phosphorylate and activate RAD51’s recruitment(61), is dephosphorylated and inactivated by PP2A(62,63), reinforcing the idea that PP2A plays an indirect role on RAD51’s activity.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the impact of PP2A on DNA Damage Response (DDR) and Homologous Recombination (HR) has also been established(2024). Multiple PP2A heterotrimers were found to be essential in directing successful HR-dependent DSBs repair(24) and the BRCA2-PP2A complex formation/stability was established to be required for DNA repair efficiency by the HR pathway in human cells(25). Therefore, PP2A seems to represent an attractive therapeutic target for the treatment of human cancers that are driven by a high degree of Genomic Instability (GI), including HGSC.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the tumor suppressor gene BRCA2 are associated with a predisposition to breast and ovarian cancers. BRCA2 has a central role in maintaining genome integrity by facilitating the repair of toxic DNA double strand breaks (DSBs) through homologous recombination (HR) ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…BRCA2 is a tumor suppressor and a key mediator of homologous recombination (HR) in vertebrates. Repair of DNA damage through homologous recombination requires BRCA2 to form complexes with MEILB2 and PP2A-B56 ( 51 , 52 ). A study by Brandsma revealed that BRCA2 formed direct and evolutionarily conserved interaction with HSF2BP, which is required for mouse spermatogenesis ( 53 ).…”
Section: Discussionmentioning
confidence: 99%